LEVELS OF HEAVY METALS IN SOME SELECTED FISH OF RIVER GONGOLA BASIN, ITS DAM AND DADINKOWA DAM, GOMBE STATE NIGERIA (FUDMA JOURNAL OF SCIENCES, 2021)
This study was carried out in ten (10) different locations within River Gongola, its Dam, and Dadinkowa Dam, Gombe State, Nigeria during the wet and dry season to study the water quality in terms of physicochemical properties to ascertain the levels of contaminants due to flooding and anthropogenic activities and the levels of heavy metals (Cr, Cd, Pb, and Ni) in the two species of fish (Clarias gariepinus and Bagrus docmak). A total of 200 water and 360 fish samples comprising two different species were collected in the month of March-June 2017 (Dry season) and July-October 2017 (Wet Season). The results of physicochemical properties obtained ranges between Temperature 29.0-30 0C and 30-32 0C, pH 5.4-7.8 and 6.0-6.9, Conductivity 93.3-161 Î¼S/cm3 and 104.9-128 Î¼S/cm3, Dissolved oxygen 1.2-3.98 mg/l and 0.4-3.1 mg/l, Total Suspended Solids 10-860 mg/l and 13-1180 mg/l, Total Dissolved Solids 46.5-80.5 mg/l and 54.2-76.5 mg/l, Turbidity 424.7-783.5 NTU and 11.15-442.1 NTU, Phosphate 1.82-7.23 mg/l and 0.00-0.11 mg/l, and Nitrate 2.25-8.82 mg/l and 2.68-6.81 mg/l during wet and dry season respectively. The result reveals that turbidity, PO43, DO, TSS, and TDS were above the acceptable permissible limits of WHO While the mean concentration levels of heavy metals in Clarias gariepinus and Bagrus docmak revealed that Cr was below the detectable limit while Cd ranges between 0.5-7.75 Âµg/g, Pb rangesbetween 3.9-35.6 Âµg/g during the wet and dry season. The mean concentrations of all the studied metals were above the permissible limit of WHO with a higher concentration during the dry season.
Keywords: Dadinkowa Dam, Fish, Heavy Metals, River Gongola